Artificial Intelligence and technological innovation - Sotiriou , Lydia; Nakhleh, Floriana (Open Schools Journal for Open Science, 2024)
AI, abbreviation for Artificial Intelligence, is all about machines mimicking human intelligence. It is used in various ways like expert systems, natural language processing, and image recognition. Sometimes, companies claim they use AI when it is just a component, like machine learning. Python, R, Java, C++, and Julia are popular programming languages for AI. AI has made huge strides since 1951, when the first AI program played checkers. IBM's Deep Blue beat a chess grandmaster in 1997. OpenAI's GPT models are another milestone. AI helps analyze data, make decisions, and has applications in healthcare, education, and in many other fields.